THE HISTORIOGRAPHY OF EARLY NEO-THOMISM AND THE STUDY OF THE VIEWS OF UKRAINIAN NEOTOMISTS OF THE FIRST HALF OF THE XX CENTURY - SHEREMETA, Oksana (Filosofska Dumka, 2024)
In the article, the author substantiates the thesis that the study of the historiography of early Neo-Thomism is extremely important for research on the history of its Ukrainian branch and, accordingly, the creation of its Ukrainian historiography. Early Neotomism is a significant stage in the development of Neotomism. Under its influence, Ukrainian neo-Thomists Andrei Sheptytsky, J. Slipyj, and M. Konrad formed their views. Its study is an important part of the historiography of Ukrainian Neo-Thomism. The study of early Neo-Thomism helps not only to objectively assess the views of Ukrainian Neo-Thomists, but also to distinguish the views of thinkers who do not belong to it, as in the case of H. Kostelnyk. The historiography of the issue includes not only the works of Ukrainian thinkers and studies devoted to their views, but also the sources of Neotomism, the works of foreign Neotomists, and studies that help to reconstruct the inherent context of the ideas of the representatives of the movement in Ukraine. The most important of these types of works are the encyclicals of the Popes and documents of the Church, the works of Neo-Thomist philosophers, and the achievements of researchers of this period. They help to recreate the context and clarify the features of early Neo-Thomism. The main one is objective idealism, which is used to criticise subjectivism in philosophy. The next feature is the reference not directly to the works of Thomas Aquinas, but to the encyclicals of the Popes, Church documents, and the works of famous Neo-Thomists. Thus, the absence of direct references to St Thomas is not a reason to think that a thinker cannot be a Neotomist. The study of early Neo-Thomism is an important part of the historiography of Ukrainian Neo-Thomism. His research will make it possible not only to objectively assess the views of Ukrainian neo-Thomists, but also to distinguish the views of thinkers who do not belong to it. As a result, it can be argued that the study of the historiography of early neo-Thomism is extremely important for research on the history of its Ukrainian branch and, accordingly, for the creation of the historiography of the issue.